2020
DOI: 10.1029/2020jb019565
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of the Chenghai Fault Zone, Yunnan, China, Constrained From Teleseismic Travel Time and Ambient Noise Tomography

Abstract: To derive high‐resolution fault zone (FZ) structure of the Chenghai fault in Yunnan, southwestern China, we deployed a linear dense array crossing the fault from January to February 2018. The array consisted of 158 short‐period (5 s) three‐component instruments and spanned an aperture of ~8 km with average station spacing of 40–50 m. During the 1‐month deployment, 20 teleseismic earthquakes with moment magnitudes larger than 5.5 and 41 local earthquakes were recorded. We first analyzed the travel times of P an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 65 publications
3
63
0
2
Order By: Relevance
“…In this study, using seismograms recorded by the same dense linear array, we further analyze local site effects related to the Chenghai fault zone as well as their spatial variabilities. As expected, ground motions caused by both local and teleseismic earthquakes are significantly amplified across the wide LVZ previously found by Yang et al (2020). Within the LVZ, we find a more localized zone of ∼500 m wide around the fault surface trace where ground motions are further amplified between ∼0.4 and 2 Hz (Figure 7a).…”
Section: An Effective Methods To Delineate Fault Zonesupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, using seismograms recorded by the same dense linear array, we further analyze local site effects related to the Chenghai fault zone as well as their spatial variabilities. As expected, ground motions caused by both local and teleseismic earthquakes are significantly amplified across the wide LVZ previously found by Yang et al (2020). Within the LVZ, we find a more localized zone of ∼500 m wide around the fault surface trace where ground motions are further amplified between ∼0.4 and 2 Hz (Figure 7a).…”
Section: An Effective Methods To Delineate Fault Zonesupporting
confidence: 85%
“…Figure 11 shows the modeled spectral ratio result along the array based on the Vs model from Yang et al (2020), from which we find that spectral ratios are higher below 1 Hz but are much lower above 1 Hz within the LVZ. As lower Vs usually corresponds to lower Q (i.e., stronger attenuation), the amplitude of higher-frequency waves would decrease considerably due to frequency-dependent attenuation.…”
Section: Sh-wave Transfer Functionmentioning
confidence: 99%
“…To focus on the local structure, we correct the topographic effects using h v j ref / , where j h are the elevations of individual stations (which vary less than 150 m across the seismic array) (Yang et al, 2020), and ref v are the inverted P-wave velocities (Figure 7). We follow the same steps in Yang et al (2020), but we use the inverted P-wave velocities as ref v for each station. After that, we select the theoretical P-wave arrival time of one reference station (located at the northwestern end of the region B in Figure 8), and calculate theoretical relative P-wave arrivals for other stations (green dots in Figure 8a) with station geometry and topography correction, similar as in Yang et al (2020).…”
Section: Comparison With P-and S-waves Travel Timesmentioning
confidence: 99%
“…Li et al (2020) revealed the high-speed intrusive rocks at shallow crust in the Tan-Lu fault zone in Lujiang, Anhui Province using dense array ambient noise tomography. Yang et al (2020Yang et al ( , 2021 found that there was a lowvelocity zone within the southern array of the Chenghai fault, Yunnan, but no such signature in the northern array using the data of the two dense linear arrays across the fault. These high-resolution fault zone images provide an important basis for earthquake rupture simulation and hazard assessment (e.g., Weng et al, 2016;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%